A Comparative Studyof Construction Sequence with Conventional Analysis (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Rising incidents of failure of buildings during the construction phase is anincreasing concern in India. The failure of structural elements like slabs, beams, columns,and shear walls is critical. Construction sequence analysis (CSA) helps in analysing thebuilding in a staged fashion. Despite its importance, our knowledge of CSA is poor, and theimplementation is imperfect. The purpose of this study is to investigate the change in valuesof numerous structural parameters namely axial force, shear force, and bending momentduring and after construction. Using CSA, this study analysed the values of structuralparameters of a 15 storied building located in Pune and measured these results against thedynamic analysis of the building. The values of deflection and shear forces found in CSA areup to 45% more than dynamic analysis. This study definitively answers the questionregarding the failure of buildings during the construction phase and how it can be avoided byusing CSA. Experimental studies are needed to establish real-world values of structuralparameters.